Comportamiento agronómico del frejol phaseolus vulgaris l. a la aplicación de abonos foliares en el cantón Balao provincia del Guayas - Cochancela Ayala, José Luis (2014)
In the Province of Guayas the Farm "Zumba" Balao town owned by Mr. Jose Zumba Naula, located 13 km from the route San Carlos – Balao, the geographic coordinates are: Length: 79o 48´36´´ W, Latitude: 02o 54´ 36´´S Altitude: 7 m., The experimental field work was carried on to study the effects of foliar fertilization in the production of beans of improved variety called “Doralisa INIAP 474”, This work was posed the following objectives: to evaluate the effect of foliar fertilizers in the cultivation of beans; to determine the best treatment for foliar fertilizer for cultivation and crop production; to Evaluate beans to the application of foliar fertilizers by analyzing economic. The treatments were T1 Green Fish 0.5 to 1 l/ha; T2. Biol 25 l/ha., Alga Fulvimax 1.0 l /ha and T4 absolute control. The response variables were, plant height to 30, 45 and 60 days. Number of pods, pod diameter, hundred seed weight, yield in kg/ha., the test area was prepared with farm machinery by deep plowing and two harrow passes, leaving for 7 days then proceeded to lift the 50 cm spaced rows. Planting: performed planting manually in the 20 cm and 50 cm between plant row a wooden spar used, placing 3 seeds per hill of beans, equivalent to later leave two plants at a seed rate of 200 million/ha., treatments were arranged in plots in a randomized block design, with four treatments and four replications totaling sixteen experimental units. The weed control was performed manually and with a machete every week. The application of the foliar fertilizer performed at 21, 36 and 51 days for four treatments design, except the witness, for this work spray equipment (CP3 pump 20 liter) was used for the implementation of Biol, Green Fish and Fulvimax Alga achieving higher performance with treatment three Fulvimax Alga 1.579kg/ha., followed by Green Fish with 1.503 kg/ha., and Biol yielding 1.448 kg/ha., being witnessed the lowest performance1.355kg/ha.